The influence of socio-economic factors on efficiency of wheat farmers in Nigeria - Jibrin, S.A.; Ali, I. M; Baba, B. A.; Mamadi, A.A. (ADAN JOURNAL OF AGRICULTURE, 2025)
The study examined the socio-economic factors influencing efficiency of wheat farmers in some wheat producing states of Nigeria. The study did not cover Borno and Yobe states wheat producing areas due to security challenges. Primary data was obtained from 866 farmers using proportionate selection of wheat farmers from the states list of farmers. A structured questionnaire and interview schedule were administered to the farmers to collect data for the study. Stochastic frontier model was used to capture wheat farmers production efficiency. Years of experience in wheat farming, extension visit, sex, level of literacy and household size were found to inversely influence technical inefficiency of respondents. There should be training and retraining of more wheat farmers to reduce technical inefficiency among wheat farmers across the wheat producing states in Nigeria.